Effect of precursor and surfactant nature on geometrical characteristics of mesoporous silicas - Pavlenko, A.N.; Yanishpolskii, V.V.; Tertykh, V.A.; Il'in, V.G.; Leboda, R.; Skubiszewska-Zieba, J. (Поверхность, 2002)
Bimodal mesoporous silicas and materials MCM-41 type were synthesized with the use as a template cationic surfactants distinguished by a length of the alkyl chain. Fumed silica, tetraethyl orthosilicate as well as of mixture these compounds were applied as a silicate precursor. Obtained samples have been characterized by the powder X-ray diffraction technique and adsorption measurements. Specific surface area, pore diameter, pore size distribution was determined from nitrogen ad(de)sorption isotherms at 77 K for the silicas prepared. The products with bimodal pore distribution have not ordered structure and contain macropores and mesopores, whose sizes are typical for MCM-41 materials. Effect of surfactant and precursor nature on the geometrical features of the ordered structure of MCM-41 type and bimodal porous materials was studied.